Aortic remodelling following the treatment and regression of hypertensive left ventricular hypertrophy: a cardiovascular magnetic resonance study. (July 2015) - Ripley, David P.; Negrou, Kalliopi; Oliver, James J.; Worthy, Gill; Struthers, Allan D.; Plein, Sven; Greenwood, John P.
Abstract Background: Increased arterial stiffness independently predicts adverse prognosis. While different antihypertensive strategies produce different magnitudes of left ventricular hypertrophy (LVH) regression, there are no comparative data on how these strategies affect arterial stiffness. The aim was to determine the longitudinal change in aortic stiffness following the treatment of essential hypertension with two mechanistically different antihypertensive treatment strategies. Methods and results: Forty-two patients with essential hypertension and CMR confirmed with LVH were randomly assigned to antihypertensive regimes for 6 months. Treatment strategies were designed either to inhibit the renin–angiotensin–aldosterone system (RAAS) and the sympathetic nervous system (SNS) (valsartan and moxonidine, group VM) or to have neutral effect on these systems (bendroflumethiazide and amlodipine, group BA). Both treatment groups underwent identical baseline and a 6-month follow-up CMR and were compared with a healthy age-matched control group. Baseline aortic distensibility (AD) was lower in both hypertensive groups compared with controls (2.8 × 10−3 mmHg−1 in group VM (p = 0.001) and 3.3 × 10−3 mmHg−1 group BA (p = 0.039) compared with 4.5 × 10−3 mmHg−1 in the control group). AD increased after antihypertensive therapy (VM: 2.8 × 10−3 mmHg−1–4.2 × 10−3 mmHg−1 (p = 0.001); BA 3.3 × 10−3 mmHg−1–4.6 × 10−3 mmHg−1 (p < 0.01)). In both treatment groups AD returned to a level comparable with the normal control group (p = 0.81) after 6 months. Conclusions: In patients with essential hypertension and LVH, AD was lower than in matched normal controls. Despite the opposing pharmacological mechanisms utilised across the treatment groups, the improvement in AD was similar, suggesting that blood pressure reduction per se may be more important than RAAS and SNS inhibition for the improvement of aortic remodelling.